Design and implementation of a Sky Quality Meter to measure light pollution in the night sky - Nurul Amirah Dinah (Nanyang Technological University, 2020)
The Sky Quality Meter (SQM) is a commonly used electrical device by both amateur as well as professional astronomers. It allows user to follow the progression of the night sky brightness. Its range of outreach is not limited to only polluted regions but also first-class astronomical observatories [1]. It is frequently used by professional astronomers to obtain readings and data of the night sky brightness. The cons of using an SQM is the expensive price, bulky design and it is non-user friendly. It is not accommodating for first-time user, as the device requires certain level of experience and expertise. Therefore, it is rarely used by amateurs. There are various methods that are available, which shows how to carry out the data collection process. The equipment and procedures implemented are determined by the scope and objective of the project, as there are certain strengths and limitations to each of the methods. The Night Sky Brightness (NSB) is an indicator used for night pollution. Its unit is : / 2(magnitude per square arcsec) [2]. To provide a more convenient and inexpensive tool, this project will focus on gathering data for Singapore’s night sky to measure the brightness of the night sky and providing an alternative simpler process as compared to using an SQM.